Wild Edible Plant Nutritional Contribution and Consumer Perception in Ethiopia - Haile Tesfaye Duguma (International Journal of Food Science)
The scarcity, high cost, and unreliable supply of healthy food in developing countries have resulted in the search for cheap and alternative sources of healthy and nutritious food. Wild edible plants (WEPs) are one of the alternative sources of healthy and nutritious food, and they are crucially important in supporting the global food basket in all parts of the world in general and in sub-Saharan Africa in particular. These wild edible plants have played a significant role in supplying food and nutritional requirements and increasing the health status of poor communities in many rural parts of the world. In Ethiopia, rural communities use wild edible plants as a means of survival especially during times of drought and famine and during other forms calamities and crises. Wild edible plants have high nutritional content, including proteins, vitamin B2, and vitamin C, which can be used as alternatives to conventional plant-based human diets. The available literature has revealed that some wild edible plants also have medicinal properties. Even though wild edible plants are important for food security, they are usually overlooked and perceived as food for poor families. This review indicates that fruits are the most commonly used WEPs, both for consumption and medicinal value, and most plant parts are eaten directly in raw forms. This review focuses on the commercial exploitation of wild edible plants as a source of dietary supplements and alternative medicines and as a means to generate income; it also focuses on consumer perception toward wild edible plants in Ethiopia. Despite easy accessibility and availability, the consumption of wild edible plants is challenged by numerous factors. This review suggests that nutrition policies have to promote the utilization of wild edible plants as one pillar of food and nutrition security. Bioactive compound contents and antinutritional factor contents of wild and medicinal plants need further investigation.